Financial dependence and intimate partner violence (IPV) among married Syrian refugee women living in non-camp settings in Jordan - Ajita Singh; Nabila El-Bassel; Neeraj Kaushal; Melissa Meinhart; Jennifer Komos Hartmann; Trena Mukherjee; Maysa’ Khadra; Ruba Jaber; Raeda Al-Qutob; Anindita Dasgupta (Journal of Global Health Reports, 2022)
# Background